Peningkatan Kompetensi Guru Taman Kanak-kanak dalam Pendampingan Belajar Anak Usia Dini melalui Penerapan Pembelajaran Daring - Nurul Renaningtias; Ferzha Putra Utama; Julia Purnama Sari (LPPM UNINUS, 2022)
Currently, all elements of society are aware of the Covid-19 virus. One aspect that is significantly affected is education. The online learning method has been done to prevent the spread of the virus in schools during the pandemic era. The implementation of online learning for all levels of education, especially in kindergarten, raises many problems such as the difficulty of teachers in teaching, the low capacity of teachers in mastering technology-based learning methods and media, and the limitation of parents accompanying their children while studying. One of the most effective media to improve student learning online is video. Through this training program, kindergarten teachers in Arga Makmur City were trained to enhance competence, insight, and knowledge. This training activity has a positive impact on the target partners. The post-test results show that 92% of teachers can operate the Kinemaster application while 60% of them can create video-based learning content.